(untitled) (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2023)
In this article, the concept of a service contract for a fee, the opinions of legal scholars on a service contract for a fee, norms related to a service contract for a fee in the legislation of the Republic of Uzbekistan, and the resolution of disputes within the framework of a service contract for a fee the concept of mediation, the problem situation and its solution are mentioned.